2007
DOI: 10.1063/1.2772192
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen detection using AlGaN∕GaN high electron mobility transistors

Abstract: Antibody-functionalized Au-gated AlGaN∕GaN high electron mobility transistors (HEMTs) were used to detect prostate specific antigen (PSA). The PSA antibody was anchored to the gate area through the formation of carboxylate succinimdyl ester bonds with immobilized thioglycolic acid. The AlGaN∕GaN HEMT drain-source current showed a rapid response of less than 5s when target PSA in a buffer at clinical concentrations was added to the antibody-immobilized surface. The authors could detect a wide range of concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 24 publications
1
69
1
1
Order By: Relevance
“…We (Shapiro et al 2007;Gupta et al 2008) and others (Kang et al 2007) have shown that the classical dismissal of planar bioFETs for protein sensing in biological buffers/fluids (Bergveld 1991;Schoening & Poghossian 2002) is inappropriate. However, the classical assessment of bioFET feasibility is correct in asserting that the distances between analyte charges and semiconductor surfaces and buffer salt concentration are inversely related to signal intensity (Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We (Shapiro et al 2007;Gupta et al 2008) and others (Kang et al 2007) have shown that the classical dismissal of planar bioFETs for protein sensing in biological buffers/fluids (Bergveld 1991;Schoening & Poghossian 2002) is inappropriate. However, the classical assessment of bioFET feasibility is correct in asserting that the distances between analyte charges and semiconductor surfaces and buffer salt concentration are inversely related to signal intensity (Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to stronger polarization constants, for the same lattice strain as in AlGaN/GaN, a higher 2DEG concentration could be achieved [7][8][9][10]. This heterostructure originally developed for high-speed devices, has recently experienced a renewed interest due to its wide and tunable band gap, strong polarization and very high sensitivity of 2DEG concentration to the surface barrier that makes it feasible to be used in reduction based applications [11], solar blind UV detectors [12,13] and molecule detectors [14][15][16] is an interest of scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…By functionalizing AlGaN/GaN HEMTs with botulinum antibodies in the gate region, we have been able to detect botulinum toxin to levels as low as 0.1 ng/ml, as shown in Figure 2 (6,7) . These sensors can be re-used after by rinsing in PBS (phosphate buffer saline) wash In a similar fashion, both Prostate Specific Antigen (PSA) (8) and breast cancer markers (c-erbB-2) (9) in saliva have been detected at clinically relevant concentrations using HEMTs functionalized with the relevant antibodies. Other biomarkers detected in breath condensate include glucose (10) and pH, as well as lactic acid, traumatic brain injury, kidney injury molecules (11) , chlorine ions (based on either InN films or AgCl deposited in the gate region) (12) and DNA in buffer solutions.…”
Section: Examples Of Gan-based Biosensorsmentioning
confidence: 99%